Notes on the integration of economic and social policy - Portocarrero, Felipe (1996)
The urgent need to achieve greater economic growth in the short term has overshadowed the importance of social policy to sustaining that growth in the long run. And, on the flip side, narrow views, thankfully overcome, that attach absolute priority to maintaining social policies based on direct and indirect transferences hand-outs that undermine macroeconomic stability, are giving way to a more balanced outlook. Now, more than ever, it is vital that national and international policy agendas have an integrated vision of the social and economic dimensions of development. Based on a number of studies, this article looks closely at the impediments and challenges that recent discussions of these issues have brought to light.